2014
DOI: 10.1088/0022-3727/47/5/055206
|View full text |Cite
|
Sign up to set email alerts
|

Simple model of the rf noise generated by multipacting electrons

Abstract: A simplified analytical model is developed to predict the spectrum of electric current induced by the multipacting electrons between two parallel electrodes exposed to an rf voltage of fixed amplitude. The model is based on the resonant multipactor theory and makes it possible to calculate the relative spectral amplitudes of electric current at different harmonics and sub-harmonics of the applied rf frequency. The theoretical predictions are confirmed by numerical simulations of multipactor inside a rectangula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Multipactor can have detrimental effects on devices' normal operation: increasing the system noise level leading to signal degradation [8], outgassing [9], raising the local temperature of the device that may damage internal components [10], loading the cavity with the build-up of an electron cloud [11], and generating undesirable harmonics [12]. If not stopped, the temperature rise, and the subsequent increase of pressure due to particles' desorption, caused by multipactor, can trigger a corona discharge which may lead to components' destruction [9], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Multipactor can have detrimental effects on devices' normal operation: increasing the system noise level leading to signal degradation [8], outgassing [9], raising the local temperature of the device that may damage internal components [10], loading the cavity with the build-up of an electron cloud [11], and generating undesirable harmonics [12]. If not stopped, the temperature rise, and the subsequent increase of pressure due to particles' desorption, caused by multipactor, can trigger a corona discharge which may lead to components' destruction [9], [13].…”
Section: Introductionmentioning
confidence: 99%
“…employed [13] the dyadic Green's function technique for computing the radiated electric field due to multipactor current in a coaxial geometry and found that a distortion in the rf field occurs within the gap due to multipactor. Later studies also showed [165–168] unwanted frequencies can be generated due to multipactor resulting in distortion of the rf signals.…”
Section: Recent Advances In Multipactor Prediction and Physicsmentioning
confidence: 99%
“…However, with increasing complexity in terms of geometry [3], [4], materials [5], [6], and surface finishing, achieving accurate multipactor simulations becomes a challenge. Modeling tools have seen large advances recently [7]- [9], and simulations with modulated signal [10], [11], space charge [12], multiple materials [13], [14], or simple noise characterization [15] are common nowadays. All of these advances in the simulation field are driving designers to request that their devices are tested against the same conditions that they were simulated-in terms of RF power, signal modulation, and temperature [16].…”
Section: Introductionmentioning
confidence: 99%